EARLY CHILDHOOD EDUCATION AS THE FOUNDATION OF LIFELONG LEARNING - Arnita Fitri; Aisyah Oktavia Siregar; Deswi Wahyuni; Hamdi Abdullah Hasibuan (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Early childhood education is not merely the initial stage of formal education, but rather a critical period that shapes individuals’ cognitive foundations, emotional maturity, and learning habits. Early childhood education plays a strategic role in fostering readiness for lifelong learning and serves as the foundation for lifelong learning. This study employed a qualitative approach focused on a literature review. The data used in this study were secondary data obtained from books, journals, and published articles. The data collection method used was a literature review. Data analysis was conducted through the stages of data collection, verification, and drawing conclusions. The results of this study indicate that the quality of learning experiences during childhood has a significant correlation with later academic achievement, psychological well-being, and economic contribution as adults. The novelty of this article lies in the emphasis that investment in PAUD is a fundamental strategy for realizing sustainable human resource development.